Argumentative Indicators in Discourse - Eemeren, Frans H. van. author. aut Link
X, 234 p.
Keywords: Argumentative Indicators: A Pragma-Dialectical Study identifies and analyses English words and expressions that are crucial for an adequate reconstruction of argumentative discourse. It provides the analyst of argumentative discussions and texts with a systematic set of instruments for giving a well-founded analysis which results in an analytic overview of the elements that are relevant for the evaluation of the argumentation. In the book a systematic connection is made between linguistic insights into the characteristics of argumentative discourse and insights from argumentation theory into the resolution of differences of opinion by means of argumentation.